Penerapan Model Prototype Untuk Pembangunan Sistem Point of Sale (POS) Pada Toko Ritel - Rara Puspa Aisyah; Amin Padmo Azam Masa; Hario Jati Setyadi (Puslitbang Sinergis Asa Professional, 2023)
Point of Sale (POS) system in the business field, especially in the field of sales in retail stores is needed. This is because POS can replace business processes from conventional to systemized using electronic devices, namely computers. Toko Kafindra currently has not implemented a computerized business process. Therefore, this research implements a POS that can help Toko Kafindra in facilitating the management of business processes so that the retail store business can grow rapidly. This research uses a prototype model to facilitate the identification of user needs for the system to be built. The results showed that the Kafindra Store POS not only made it easier for the owner to know the outgoing goods but also could make it easier for the owner to know the incoming goods using the system of purchasing goods to suppliers. In addition, based on the results of the blackbox test on the system, the test results are valid and the system functions properly